Ekspansi termal linier dan residu malam inlei gigi dengan komponen parafin Indonesia - Dyah Irnawati; Widjijono Widjijono; Harsini Harsini (Jurnal Teknosains, 2020)
Inlay wax is used for pattern of metallic inlays, crowns, and fixed partial dentures. Inlay wax must have a linear thermal expansion (LTE) and a residue that comply the standards. Inlay wax contains paraffin, carnauba, and beeswax. Paraffin and beeswax are produced in Indonesia. This study aims to examine the effect of the inlay wax compositions with paraffin and beeswax Indonesia on the LTE and residue properties. The research materials are paraffin (Pertamina, Balikpapan), beeswax (SEA, Yogyakarta), carnauba wax (Brataco Chemicals, Yogyakarta), and inlay wax (GC, Japan). Five inlay wax compositions are made with a ratio of paraffin, carnauba, and beeswax 60: 35: 5 (K-60), 65: 30: 5 (K-65), 70: 25: 5 (K-70), 75:20 : 5 (K-75), and 80: 15: 5 (K-80) (% w/w). The waxes were melted at 75 ± 5 oC then moulded for the TLE (267x6.35 x6.35 mm) and the residue (1 g) test specimens (n=4). The LTE and residue specimens were also made of paraffin, carnauba wax, beeswax, and commercial wax (n = 4). The LTE and residue tests were carried out based on ANSI/ADA specification No.4. Data were statistically analyzed by analysis of variance and LSD (α = 0.05). Anava test results showed that composition and temperature had a significant effect on LTE (p <0.05) and composition had a significant effect on residues (p <0.05). The LSD test results showed a significant difference in LTE of the K-75 group with other groups and the residues of the K-75 group and K-80 group with other groups (p <0.05). Inlay wax compositions with high paraffin concentrations have high LTE and residue. The value of LTE and residue of inlay wax with paraffin and beeswax from Indonesia are in accordance with the ANSI/ADA specification no. 4.